Can care coordination across levels be improved through the implementation of participatory action research interventions? Outcomes and conditions for sustaining changes in five Latin American countries - Ingrid Vargas; Pamela Eguiguren; Amparo-Susana Mo; Isabella Samico; Fernando Bertolotto; Julieta López-Vázquez; María-Luisa Vázquez (BMC, 2020)
Abstract Background Finding new strategies for care integration has become a policy priority for many fragmented health systems in Latin America. Although the implementation of interventions through a participatory action research (PAR) approach is considered to be more effective in achieving organizational change, its application is scarce. This study, part of the research project Equity-LA II, aims to analyze the impact of PAR interventions on care coordination across levels, and key aspects for their sustainability and transferability, from the stakeholder viewpoint in healthcare networks of Brazil, Chile, Colombia, Mexico and Uruguay. Different interventions were designed and implemented through a PAR process to improve communication and clinical agreement between primary care and secondary care doctors: joint meetings to discuss clinical cases and/or training; shared care guidelines; offline virtual consultations; a referral and reply letter; and an induction program. Methods A qualitative, descriptive-interpretative study was conducted in the healthcare network of each country. Focus groups and semi-structured individual interviews were conducted with a criterion sample of participants: local steering committee (29) and professional platform members (28), other health professionals (49) and managers (28). Thematic content analysis was conducted, segmented by country and type of intervention. Results Informants highlighted that joint meetings based on reflexive methods contributed substantially to improving contextually relevant elements of clinical management coordination - communication in patient follow-up, clinical agreement, appropriateness of referrals - and also administrative coordination. The meetings, alongside the PAR process, also helped to improve interaction between professionals - knowing each other personally and mutual trust - thus fostering willingness to collaborate. The PAR approach, moreover, served to spread awareness of the coordination problems and need for intervention, encouraging greater commitment and interest in participating. No noteworthy contributions were identified in remaining interventions due to low uptake. A necessary condition for the sustainability and replicability was that PAR process had to be used appropriately in a favourable context. Conclusions Evidence is provided on the substantial contribution of interventions to improving locally relevant clinical coordination elements and professional interaction when implemented through an adequate PAR process (in terms of time, method and participation levels), a necessary condition for their sustainability and replicability.